2019
DOI: 10.1186/s13071-019-3783-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of reproductive damage in the epididymis of male Kunming mice induced by chronic infection of Toxoplasma gondii PRU strain

Abstract: BackgroundSome researchers have reported that Toxoplasma gondii can cause serious reproductive impairment in male animals. Specifically, T. gondii destroy the quality of sperm in the epididymis, which affects their sexual ability. However, among such studies, none have investigated the male reproductive transcriptome. Therefore, to investigate the relationship between T. gondii and sperm maturation, we infected mice with T. gondii prugniaud (PRU) strain and performed transcriptome sequencing of the epididymis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Nonetheless, H-subcluster-specific KEGG pathways related to immune responses against T. gondii infection were still found, especially in subcluster H2. As previously reported [ 30 , 55 , 56 ], cytokine–cytokine receptor interaction (ssc04060) was found to be involved in immunomodulation of the host during acute and chronic T. gondii infection in the current study. A total of 52 genes of the pathway involving chemokines including CC and CXC subfamilies, class I helical cytokines, class II helical IL10/28-like cytokines, IL1-like cytokines, IL17-like cytokines, TNF family, and TGF-β family were potentially targeted by 31 miRNAs in subcluster H2 (Additional file 17 : Table S16).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Nonetheless, H-subcluster-specific KEGG pathways related to immune responses against T. gondii infection were still found, especially in subcluster H2. As previously reported [ 30 , 55 , 56 ], cytokine–cytokine receptor interaction (ssc04060) was found to be involved in immunomodulation of the host during acute and chronic T. gondii infection in the current study. A total of 52 genes of the pathway involving chemokines including CC and CXC subfamilies, class I helical cytokines, class II helical IL10/28-like cytokines, IL1-like cytokines, IL17-like cytokines, TNF family, and TGF-β family were potentially targeted by 31 miRNAs in subcluster H2 (Additional file 17 : Table S16).…”
Section: Discussionsupporting
confidence: 82%
“…This indicates that the interactions amongst cytokines play a crucial role in the balance of the immune microenvironment during the different infection stages, such as preventing excessive immunity in acute infection and maintaining the level of inflammation to control the reactivation of T. gondii in chronic infection. In addition, several previous researchers found that the cytokine–cytokine receptor interaction pathway was also influenced by different T. gondii strains during challenge in various infection models including cat, mouse, and human cells [ 30 , 55 , 56 ], suggesting a common feature wherein interactions between cytokines and cytokine receptors have extremely important roles in the host immune responses against T. gondii , and are not strictly host-specific or strain-specific. Nonetheless, our analysis revealed that miRNAs in subcluster H2 involved in the cytokine–cytokine receptor interaction pathway may be the important immunomodulatory molecules of the host during T. gondii infection.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, the product is catalyzed by pgk to produce glycerate 3-phosphate (3-PG) and ATP [ 30 ]. pgk is the first regulator of ATP production and plays an important role in energy production [ 31 ]. Based on this pathway, proteins were highly distributed in the glycolytic pathway, which affected energy production.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphoglycerate mutase (PGAM) is an essential glycolytic enzyme for the spermatozoa energy supply [28]. PGAM2 is the key determinant to maintaining sperm motility and morphology because it is associated to the brous sheath of the main segment within the sperm agellum [29]. The overexpression of PGAM2 interferes with mitochondrial function and this can affect fatty acid metabolism [30].…”
Section: Discussionmentioning
confidence: 99%